2016
DOI: 10.1177/1069072716652891
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Support Effects on Career Agency and Occupational Engagement Among Young Adults

Abstract: Interactive support effects on career agency and occupational engagement among young adults Abstract:The PIC model by Gati and Asher describes three career decision making stages: pre-screening, in-depth exploration, and choice of career options. We consider the role that three different forms of support (general career support by parents, emotional/instrumental support, and informational support) may play for young adults in each of these three decision-making stages.The authors further propose that different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The proactive personality trait plays an important role in both career-and organization-related constructs . Previous studies (Cooper-Thomas, Paterson, Stadler, & Saks, 2014;Jenkins & Jeske, 2015) found that proactive personality is positively associated with new employees' learning and work engagement . Seibert, Crant, and Kraimer (1999) found that proactive personality partially predicted employees' objective and subjective career successes .…”
Section: The Relationship Between Proactive Personality Cdse and Cssementioning
confidence: 87%
“…The proactive personality trait plays an important role in both career-and organization-related constructs . Previous studies (Cooper-Thomas, Paterson, Stadler, & Saks, 2014;Jenkins & Jeske, 2015) found that proactive personality is positively associated with new employees' learning and work engagement . Seibert, Crant, and Kraimer (1999) found that proactive personality partially predicted employees' objective and subjective career successes .…”
Section: The Relationship Between Proactive Personality Cdse and Cssementioning
confidence: 87%
“…This validity is supported by Guardado (2019) who argued that engaging in occupational behaviors helps individuals have a clearer understanding of their future work and feel more confident when making career-related decisions. However, Jenkins and Jeske (2017) revealed that although the two variables had a negative relationship, career indecisiveness was not a significant predictor of occupational engagement. Consequently, the results support that the OES-S has discriminant scale validity in the Turkish form.…”
Section: Discussionmentioning
confidence: 84%
“…Parents do not have a direct influence on their children regarding what exactly to study at university, but they do have an influence on the enhancement of self-confidence and self-efficacy in the process [10,11,19], strengthening self-esteem, and the importance of "me" through success [63], as evidenced by our conclusion that the decision to take the PEvAU is influenced by families, and specifically parents. They influence career decision-making regardless of whether each individual goes through processes of both formal and informal learning, as well as self-directed learning, in the sense that they structure their own decision-making as they progress through their own journey of figuring out how to best make their own decision [64].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, mothers have more influence on daughters [29,39], especially when compared to the influence that fathers have on their sons, although sons are more influenced by their father, and daughters by their mothers. This rule does not deny the existence of studies where this relationship between parents and children is not confirmed [64]. From psychosocial factors that influence student decision-making, adolescents are indecisive, which in some cases makes parents lead their children to choosing a career that does not fit their personality [9][10][11][12].…”
Section: Discussionmentioning
confidence: 99%